Relationship between Positive Body Image and Selective Visual Self-presentation on Social Networking Sites: Moderating Role of Gender - Ahadzadeh, Asharf Sadat; Ong, Fon Sim; Pahlevan Sharif, Saeed (Makara Human Behavior Studies in Asia, 2023)
This study examines the association between positive body image and selective visual self-presentation behaviors on social networking sites, while also considering the moderating influence of gender. We conducted a cross-sectional survey involving 282 undergraduate students in Malaysia (Mage = 20.85, SD = 1.81). The results reveal a negative correlation between positive body image and behaviors such as posing in pictures and editing photos. However, no significant relationship was found between positive body image and photo selection. Gender differences were evident, with females exhibiting higher engagement in posing in pictures, editing, and photo selection compared to males. The findings also show that gender plays a moderating role in the relationship between positive body image and photo selection, whereas no moderating effect was observed for posing in pictures and editing photos. The study’s implications are discussed.